2021
DOI: 10.1080/17512786.2021.1910981
|View full text |Cite
|
Sign up to set email alerts
|

Complexity, Objectivity, and Shifting Roles: Environmental Correspondents March to a Changing Beat

Abstract: Environmental journalists have been at the forefront of news industry changes. Over the past 30 years, they have had to deal with a range of challenges, including increased complexity, greater reliance on data, exposure to online negativity, and cooption into polarised political debates. At the same time, they have been among the most vulnerable to newsroom cutbacks. This exploratory study examines the extent to which environmental journalists can be considered emblematic of challenges facing beat journalism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Faced with this hostile reporting environment, journalists in the UK, Ireland and the US have also reported that environmental issues are becoming more difficult to explain. As climate science becomes more complex, journalists often require help from academics and external sources (Robbins and Wheatley 2021).…”
Section: News Coverage Of Extreme Weather Events and Eea Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Faced with this hostile reporting environment, journalists in the UK, Ireland and the US have also reported that environmental issues are becoming more difficult to explain. As climate science becomes more complex, journalists often require help from academics and external sources (Robbins and Wheatley 2021).…”
Section: News Coverage Of Extreme Weather Events and Eea Studiesmentioning
confidence: 99%
“…The advocacy role was found to be particular present among online journalists and digital-born news media in the USA (Tandoc and Takahashi 2014). However, environmental journalists from the UK, Ireland and the US who were interviewed by Robbins and Wheatley (2021) took a strong stance against an advocacy role, arguing that "reporting evidence and scientific reality does not equate to advocacy" (12). Thus, considering the various manifestations of role perceptions among climate/environmental journalists, we were interested in how journalists perceive their role specifically with regard to extreme weather event reporting.…”
Section: News Coverage Of Extreme Weather Events and Eea Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence (see above, e.g. (Brüggemann and Engesser 2017;Hiles and Hinnant 2014;Robbins and Wheatley 2021)), that over the years, climate journalism learnt to go beyond false balance and towards interpretive coverage when dealing with the denial of basic facts related to climate change. Yet, interpretive coverage would mean more, going beyond reporting events towards discussing issues in order to get a grip on the long-term process of environmental degradation.…”
Section: Transforming Journalism On Different Dimensionsmentioning
confidence: 99%